Wpływ Impulsowego Działania Obciążenia na Ugięcia Dynamiczne Małych Mostów Drogowych - Głomb, J.; Weseli, J. (Engineering Transactions, 1965)
The object of the consideration is the dynamic action of a vehicle on a small road bridge. Such a bridge is loaded by a single harmonic impulse. The differential equation of dynamic deflection is derived and discussed. Dynamic and Static deflections are compared. After qualitative analysis some conclusions are drawn on the «dynamic addition» for such bridges. In the final part of the paper the applicability range of the solution is discussed.